2005
DOI: 10.1158/0008-5472.can-05-1343
|View full text |Cite
|
Sign up to set email alerts
|

A Tumorigenic Subpopulation with Stem Cell Properties in Melanomas

Abstract: Recent studies suggest that cancer can arise from a cancer stem cell (CSC), a tumor-initiating cell that has properties similar to those of stem cells. CSCs have been identified in several malignancies, including those of blood, brain, and breast. Here, we test whether stem cell-like populations exist in human melanomas. In f20% of the metastatic melanomas cultured in growth medium suitable for human embryonic stem cells, we found a subpopulation of cells propagating as nonadherent spheres, whereas in standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
907
5
25

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,173 publications
(961 citation statements)
references
References 53 publications
24
907
5
25
Order By: Relevance
“…Similar to normal stem cells, CSCs can reproduce themselves through the process of self-renewal, which can be studied in serial transplantation assays. Additionally, cancers derived from purified CSCs recapitulate the heterogeneous phenotypes of the parental cancer from [32,47] (ii) c-Kit + Thy1 low Sca1 + Lin - [134,135] Breast (ii) CD24 med CD49f hi [6] (i) CD44 + CD24 -/low ESA + Lin - [33] (ii) CD29 hi CD24 + Lin - [7] Brain (i) CD133 + Lin - [41] (i) CD133 + [34][35][36] Lung (ii) Sca-1 + CD34 + Lin - [5] (ii) Sca-1 + CD34 + Lin - [5] Skin (ii) CD34 + CD71 low α6-integrin high [136] (i) CD20 + [137] Prostate (i) CD133 + a2b1 hi [138] (i) CD44 + α2β1 hi CD133 + [139] www.cell-research.com | Cell Research Feng Li et al npg which they were derived, reflecting the differentiation capacity of CSCs [32,33]. These observations suggest that CSCs contain the complete genetic programs necessary to initiate and sustain tumor growth.…”
Section: Discovery and Properties Of Cscsmentioning
confidence: 99%
“…Similar to normal stem cells, CSCs can reproduce themselves through the process of self-renewal, which can be studied in serial transplantation assays. Additionally, cancers derived from purified CSCs recapitulate the heterogeneous phenotypes of the parental cancer from [32,47] (ii) c-Kit + Thy1 low Sca1 + Lin - [134,135] Breast (ii) CD24 med CD49f hi [6] (i) CD44 + CD24 -/low ESA + Lin - [33] (ii) CD29 hi CD24 + Lin - [7] Brain (i) CD133 + Lin - [41] (i) CD133 + [34][35][36] Lung (ii) Sca-1 + CD34 + Lin - [5] (ii) Sca-1 + CD34 + Lin - [5] Skin (ii) CD34 + CD71 low α6-integrin high [136] (i) CD20 + [137] Prostate (i) CD133 + a2b1 hi [138] (i) CD44 + α2β1 hi CD133 + [139] www.cell-research.com | Cell Research Feng Li et al npg which they were derived, reflecting the differentiation capacity of CSCs [32,33]. These observations suggest that CSCs contain the complete genetic programs necessary to initiate and sustain tumor growth.…”
Section: Discovery and Properties Of Cscsmentioning
confidence: 99%
“…The Notch pathway mediates tissue differentiations and homeostasis by controlling stem cells. Interestingly, recent studies indicated that melanoma contains a subpopulation of tumor stem cells that can differentiate into multiple cell lineages and contribute to tumor progression (Fang et al, 2005;Grichnik et al, 2006). It is likely that aberrant Notch pathway participated in the tumorigenesis of melanoma by regulating tumor stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that the cancer stem cells survive conventional treatment to later re-emerge more resistant to therapy (Reya et al, 2001). To date, putative cancer stem cells have been identified in blood (Bonnet and Dick, 1997), brain (Singh et al, 2004), breast (Al-Hajj et al, 2003), lung (Kim et al, 2005), skin (Fang et al, 2005), pancreas (Li et al, 2007), colon (O'Brien et al, 2007;Ricci-Vitiani et al, 2007), and prostate (Collins et al, 2005;Patrawala et al, 2006).…”
mentioning
confidence: 99%